A Study of Bacteriological Profiles, Biofilm Production, and Antibiotic Susceptibility among Isolates of Chronic Suppurative Otitis Media at a Tertiary Care Hospital - Dimpal Goyal; Nita Pal; Yash Agrawal; Saroj Hooja (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background: Chronic suppurative otitis media (CSOM) is defined as chronic inflammation of the middle ear and mastoid mucosa. Biofilms act as non-selective physical barriers that obstruct antibiotic diffusion and hinder immune responses facilitating chronic bacterial infections and antibiotic resistance. Aims and Objectives: To study biofilm production among bacteria causing CSOM and their antibiotic resistance. Materials and Methods: This hospital-based descriptive type of observational study was done in the ENT department and Department of Microbiology. Ear discharge samples from 100 clinically diagnosed CSOM patients were collected and processed. Bacterial isolates were identified, and drug susceptibility testing was done using the Kirby–Bauer disc diffusion method. Biofilm production was detected by the microtiter plate method. Results: Among 100 patients included in the study, the most predominant isolate was Staphylococcus aureus (44.0%), followed by Pseudomonas aeruginosa (36.0%). Biofilm production was detected in 59.0% of isolates. Biofilm production was observed in 97.7% S. aureus isolates. Among Gram-negative isolates, biofilm production was observed in 40.0% of Klebsiella spp., 36.0% P. aeruginosa, and 22.2% E. coli. All isolates of S. aureus were susceptible to vancomycin, tigecycline, and linezolid (100%). Methicillin resistance was found in 25.6% S. aureus isolates. A susceptibility of 100% was observed with colistin and piperacillin-tazobactam among P. aeruginosa isolates. Conclusion: Ear discharge should be sent for culture and antibiotic susceptibility testing before initiation of empirical antibiotic treatment. Biofilm production is frequently associated with multi-drug resistance, so it should be tested routinely in laboratories. This will help in effective management of CSOM, prevent development of complications, and thereby prevent deafness.